2017
DOI: 10.1136/bmjopen-2016-015344
|View full text |Cite
|
Sign up to set email alerts
|

Bubble continuous positive airway pressure in the treatment of severe paediatric pneumonia in Malawi: a cost-effectiveness analysis

Abstract: ObjectivesPneumonia is the largest infectious cause of death in children under 5 years globally, and limited resource settings bear an overwhelming proportion of this disease burden. Bubble continuous positive airway pressure (bCPAP), an accepted supportive therapy, is often thought of as cost-prohibitive in these settings. We hypothesise that bCPAP is a cost-effective intervention in a limited resource setting and this study aims to determine the cost-effectiveness of bCPAP, using Malawi as an example.DesignC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…United States (n = 7), Germany (n = 4) or other European countries (n = 6). Only two studies were conducted in a low and middle income country context (Malawi and Malaysia) [25,26]. Studies were mainly conducted from a hospital/government, health system, or third party perspective (n = 14), while two studies reported a broader societal perspective [27,28].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…United States (n = 7), Germany (n = 4) or other European countries (n = 6). Only two studies were conducted in a low and middle income country context (Malawi and Malaysia) [25,26]. Studies were mainly conducted from a hospital/government, health system, or third party perspective (n = 14), while two studies reported a broader societal perspective [27,28].…”
Section: Resultsmentioning
confidence: 99%
“…The sample size of included studies ranged from 28 to 2,283 (median 337). Most studies considered adults (n = 15; mean age ranged from 48–72 years); two studies were based on under-five children [25,26] and one study considered all age groups [29]. Publication years ranged from 1998 to 2017, with 84% (n = 16) of the studies published before the publication of the CHEERs checklist in 2013.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations